2003
DOI: 10.1002/jbm.a.10105
|View full text |Cite
|
Sign up to set email alerts
|

In vivo biocompatibility of three different chemical compositions of Ricinus communis polyurethane

Abstract: Alteration in the chemical composition of a biomaterial may be undertaken to improve its biological properties. The aim of this work was to evaluate the biocompatibility of three chemical compositions of Ricinus communis polyurethane (RCP): RCPp (pure RCP), RCP + CaCO(3), and RCP +Ca(3)(PO(4))(2). RCP cylinders were surgically implanted in rabbit femurs. After 8, 12, and 16 weeks, the femurs were removed, fixed, sectioned, ground, and stained by Stevenel's blue/Alizarin red S for light microscopy and histomorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 15 publications
1
30
0
4
Order By: Relevance
“…Many studies 5,7,10 point out the advantages of using castor oil polymer as a framework for bone growth, however, castor oil polymer integrates itself to the receiving bone in a slower and more incomplete manner when compared to autogenous bone graft 15 , especially for not displaying specific biological traits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies 5,7,10 point out the advantages of using castor oil polymer as a framework for bone growth, however, castor oil polymer integrates itself to the receiving bone in a slower and more incomplete manner when compared to autogenous bone graft 15 , especially for not displaying specific biological traits.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have shown the applicability in vivo 5,6 and the benefits for castor oil polymer in vitro 7,8 , revealing the biocompatibility, osteointegration and, mainly, the diameter, conformation and intercommunication of the pores as the most important aspects to regulate vascular and cellular migration to the inside of these implants, allowing for bone neoformation.…”
Section: Introductionmentioning
confidence: 99%
“…Since, in the late 1930s, Otto Bayer and co-workers discovered and patented the chemistry of polyurethanes, these materials have found an increasingly outstanding position among the most important organic polymers for intensive technological applications [1][2][3]. Polymerized urethane resins represent a product of chemical reaction between an isocyanate and a hydroxyl group [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…This resin is commercially available with the brand name "COR -Composto Óleo de Rícino" [25] . Barros et al [26] evaluated biocompatibility of polyurethane resin (pure), the polyurethane resin with calcium carbonate and with calcium phosphate. The materials were made in cylindrical form and were randomly placed in defects created in rabbit femur.…”
Section: -Qualitative Histologic Evaluation Of the Tissue Reaction Tomentioning
confidence: 99%